The contribution of work motivation and school work climate on school counselor performance - Lisnanora Lisnanora; A Muri Yusuf; Sufyarma M (Jurnal Aplikasi IPTEK Indonesia, 2018)
This study originated from research findings and interviews with several people teacher guidance and counseling in SMP South Coastal District which revealed that the performance of teacher guidance and counseling have not described a success made in carrying out their duties and responsibilities, one of them in implementing the guidance and counseling program in schools. The success of guidance and counseling teacher performance can be affected byfactors. Some of these factors is the work motivation and school work climate. There fore, researcher wanted to describe: (1) the performance of guidance and counseling teachers, work motivation, and school work climate, (2) the contribution of work motivation on guidance and counseling teacher performance, (3) contribution of school work climate to the guidance and counseling teacher  performance, and (4) the contribution of work motivation and school work climate on guidance and counseling teacher performance. This study was quantitative research with correlational method. The population research were all counseling teachers at SMP Payakumbuh City whose S.1 guidance and counseling educational background totaling 40 people, the sample were 40 people were selected by total sampling technique. The instrument that was used in this research was the Likert scale. Data were analyzed with simple regression and multiple regression. The findings showed that: (1) in average, the performance of teachers' guidance and counseling are in good enough category, the work motivatio non high category, and school work climate are in good enough, (2) there is contribution of work motivation on teacher performance guidance and counseling 20.8% (r= 0.457. significance 0.003), (3) contribution of school work climate on guidance and counseling teacher performance amounted to 10.72% (r= 0.327, significance 0.039), and 4) there is a contribution of work motivation and school work climate together on teacher performance guidance and counseling were 27% (R= 0.520, significance 0.003). The study results representan input forguidance and counseling teacher, and teachers further enhance employe school work climate and performancein performing their duties and responsibilities as teacher guidance and counseling in school.